The impact of the carrier envelope phase-dependence on system and laser parameters - Reinhard, Paul-Gerhard; Suraud, E.; Meier, C. (Journal of Physics B-Atomic Molecular and Optical Physics, 2018)
We investigate, from a theoretical perspective, photoemission of electrons induced by ultra-short infrared pulses covering only a few photon cycles. In particular, we investigate the impact of the carrier envelope phase of the laser pulse which plays an increasingly large role for decreasing pulse length. As key observable we look at the asymmetry of the angular distribution as function of kinetic energy of the emitted electrons. The focus of the present study lies on the system dependence of the reaction. To this end, we study two very different systems in comparison, an Ar atom and the Na+9 cluster. The study employs a fully quantum-mechanical description of electron dynamics at the level of time-dependent density functional theory. We find a sensitive dependence on the system which can be related to the different spectral response properties. Results can be understood from an interplay of the ponderomotive motion driven by the external photon field and dynamical polarization of the system.
CRIS-Team Scopus Importer:2021-07-19
Keywords: angular resolved photoelectron spectra; carrier envelope phase; short laser pulses; sodium cluster